2009
DOI: 10.1002/jmri.21836
|View full text |Cite
|
Sign up to set email alerts
|

Toward a practical protocol for human optic nerve DTI with EPI geometric distortion correction

Abstract: Purpose: To develop a practical protocol for diffusion tensor imaging (DTI) of the human optic nerve with echo planar imaging (EPI) geometric distortion correction. Materials and Methods:A conventional DTI protocol was modified to acquire images with fat and cerebrospinal fluid (CSF) suppression and field inhomogeneity maps of contiguous coronal slices covering the whole brain. The technique was applied to healthy volunteers and multiple sclerosis patients with and without a history of unilateral optic neuriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 27 publications
3
30
1
Order By: Relevance
“…In both figures, the ROI positions (four pixels in size) are indicated in red. Healthy control mean optic nerve MD and FA values measured using the standard acquisition protocol (ii) were consistent with previous measurements made at 1.5T (Chabert et al, 2005;Trip et al, 2006;WheelerKingshott et al, 2006) and 3T (Kolbe et al, 2009;Naismith et al, 2009;2010;Smith et al, 2011;Techavipoo et al, 2009;Wang et al, 2011;Xu et al, 2007). …”
Section: Sequence Validation In Healthy Controls and Multiple Sclerossupporting
confidence: 74%
See 2 more Smart Citations
“…In both figures, the ROI positions (four pixels in size) are indicated in red. Healthy control mean optic nerve MD and FA values measured using the standard acquisition protocol (ii) were consistent with previous measurements made at 1.5T (Chabert et al, 2005;Trip et al, 2006;WheelerKingshott et al, 2006) and 3T (Kolbe et al, 2009;Naismith et al, 2009;2010;Smith et al, 2011;Techavipoo et al, 2009;Wang et al, 2011;Xu et al, 2007). …”
Section: Sequence Validation In Healthy Controls and Multiple Sclerossupporting
confidence: 74%
“…Another approach was proposed by Andersson et al (2003) to correct for susceptibility distortions in SE-EPI images; this required two sets of data: one acquired with the phase-encoding direction reversed, plus a B0 map, however, it may not be feasible for application in the optic nerve. Techavipoo et al (2009) used a conventional single-shot SE-EPI protocol with parallel imaging factor 2.5 and additional field inhomogeneity maps covering the whole brain with a voxel size of 1.5mmx1.5mm, and 3mm slices, and found that optic nerve tractography became feasible with geometric distortion correction. However, DTI measures were not significantly different when calculated with or without the use of distortion correction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 However, our measurements of FA, ʈ , and Ќ were not lower than those in other reports. 20 This may be ascribed to a higher b-value (b ϭ 1000 s/mm 2 ) and resolution (0.90 ϫ 0.90 ϫ 2 mm 3 ) with fat suppression to increase the accuracy of measurement, twice-refocused SE with a bipolar gradient in the EPI sequence to reduce eddy currents, and parallel imaging (GRAPPA, IPAT factor ϭ 2) to accelerate the image acquisition and reduce distortion. Second, cardiac gating was not implemented in the current protocol, so the protocol may contain errors from different cardiac cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Chabert et al 19 used another type of acquisition method (non-Care-Purcell-Meiboom-Gill fast spin-echo) and obtained results very similar to those of Wheeler-Kingshott. 17 A conventional DTI protocol was modified by Techavipoo et al 20 to acquire images with fat and CSF suppression and field inhomogeneity maps of contiguous coronal sections covering the whole brain. The technique was applied to healthy volunteers and patients with multiple sclerosis with and without a history of unilateral optic neuritis.…”
Section: Discussionmentioning
confidence: 99%